Effect of palm cooking oil as processing aids in biodegradable low density polyethylene (LDPE)/tapioca starch blends - Rasit Ali, Roshafima; Wan Abdul Rahman, Wan Aizan (2007)
The aim of this works is to study the effect of palm cooking oil as processing aid in biodegradable/tapioca starch packaging film. A blends of low density polyethylene (LDPE)/tapioca were prepared by twin screw extrusion with the addition of glycerol and palm cooking oil as processing aids. Studies on their melt flow properties and thermal stability were carried out by melt flow index analysis and thermogravimetry analysis respectively. Melt flow index of LDPE/TS:90/10 with addition of glycerol and palm cooking oil are higher than MFI value of LDPE. This indicated that incorporation of glycerol and palm cooking oil as processing aids increase the melt flow index of the blends compared to neat LDPE. Addition of palm cooking oil as processing aid in the blend also increased thermal stability of the polymer.